Identification of The Effectiveness of The Leadership Development Program for Hospital X Managers - Qolbi, Nazmi Nurul; Ariyani, Nurul Dwi (International Journal of Psychology and Health Science, 2025)
This study aims to evaluate the effectiveness of a leadership development training program for managers at Hospital X using the Kirkpatrick Model, which includes four levels: reaction, learning, behavior, and results. The research employed a descriptive qualitative approach, collecting data through open-ended questionnaires completed by 22 managers/unit heads. The findings indicate that participants responded positively to all aspects of the training. They expressed satisfaction with the clarity of objectives, the relevance of the material, the interactive learning methods, and the competence of the facilitators. Additionally, participants reported an increase in knowledge and skills, positive behavioral changes in the workplace, and a perceived improvement in unit performance. Recommendations include the addition of practical sessions, follow-up coaching, and quantitative impact evaluations to ensure more measurable and sustainable outcomes. This study contributes to the improvement of leadership training quality in the healthcare sector.